(untitled) (Research, Society and Development, 2020)
The objective of the case study is to describe the implementation of improvements in the back-office area, thus enabling the increase of performance in the execution of demands and deliveries to internal and external clients of a small consulting company located in São Paulo, the capital. through the application of a 5w2h action plan and time management concepts along with other methodologies such as mind map for bottleneck identification and BPA (business process analysis) to model existing workflows and enable systemic improvements, setting goals and indicators to measure the final gains of the implementation in the organization, work deployed and monitored for two months. the results obtained during the work, such as a 14% increase in delivery capacity, 18% reduction in rework rate and 16% in late delivery, clarify the importance and feasibility of applications of such concepts in areas that deal with deliveries, thus highlighting the relevance of continuous improvements to the organizational, strategic and competitive evolution in the market. the positive impacts of this work permeate the organization, the research group, and the institution where it is inserted.